2003
DOI: 10.1046/j.1365-3024.2003.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Metalloendopeptidases from the intestinal brush border of Haemonchus contortus as protective antigens for sheep

Abstract: Substantial protection against the economically important nematode Haemonchus contortus has been achieved by immunizing sheep with a glycoprotein fraction isolated from the intestinal membranes of this parasite. This fraction has been termed Haemonchus galactose-containing glycoprotein complex (H-gal-GP) since it was originally isolated through its selective binding to lectins with a specificity for N-acetylgalactosamine. A major component of this highly protective antigen complex is a family of four zinc meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 19 publications
3
45
0
1
Order By: Relevance
“…MEP3 alone or MEPs 1, 2 and 4 in combination, electro-eluted from the complex following SDS gel electrophoresis, each reduced egg counts by about 30%. 32 These data indicated that the MEPs all contributed to the protection induced by H-gal-GP. Protection was lost when sheep were immunized with fully reduced and denatured H-gal-GP or with bacterially-expressed recombinant forms of MEP 1 or the principal domains of MEP3, suggesting that conformational epitopes on the MEPs are required for immunity.…”
Section: H11mentioning
confidence: 84%
See 1 more Smart Citation
“…MEP3 alone or MEPs 1, 2 and 4 in combination, electro-eluted from the complex following SDS gel electrophoresis, each reduced egg counts by about 30%. 32 These data indicated that the MEPs all contributed to the protection induced by H-gal-GP. Protection was lost when sheep were immunized with fully reduced and denatured H-gal-GP or with bacterially-expressed recombinant forms of MEP 1 or the principal domains of MEP3, suggesting that conformational epitopes on the MEPs are required for immunity.…”
Section: H11mentioning
confidence: 84%
“…Protection was lost when sheep were immunized with fully reduced and denatured H-gal-GP or with bacterially-expressed recombinant forms of MEP 1 or the principal domains of MEP3, suggesting that conformational epitopes on the MEPs are required for immunity. 32 Another component of H-gal-GP was shown to be an aspartyl protease with homology to mammalian pepsinogen sequences (HcPEP1), again expressed on the luminal surface of the gut in the blood-feeding stages. 25 The enzyme was shown to be almost exclusively expressed by the blood-feeding parasite stages.…”
Section: H11mentioning
confidence: 99%
“…The sheep barber's pole worm, Haemonchus contortus, expresses a family of metalloproteases in the intestine (43,44); although these enzymes have not been expressed in active form, it is thought that they are involved in Hb digestion. MEP-1 displayed a broad pH range when assessed in zymograms.…”
Section: Ac-apr-1 Ac-cp-2 and Ac-mep-1 Degrade Hb In A Semiorderedmentioning
confidence: 99%
“…Haemonchus galactose-containing glycoprotein is a protein complex from the intestine of the sheep barber's pole worm, H. contortus. Vaccination of sheep with H-gal-GP confers high levels of protection against parasite challenge; the complex is predominantly made up of aspartic, cysteine, and metalloproteases (57), and recent evidence suggests that the purified enzymes from Haemonchus galactose-containing glycoprotein are responsible for the vaccine efficacy (44,58,59). We recently described the efficacy of Ac-CP-2 as an anti-hookworm vaccine in dogs experimentally challenged with A. caninum (21).…”
Section: Ac-apr-1 Ac-cp-2 and Ac-mep-1 Degrade Hb In A Semiorderedmentioning
confidence: 99%
“…Recombinant DNA technology allows production of large amounts of parasite antigens in a heterologous system with high level of purity. Several attempts exploiting the recombinant versions of H11 (Reszka et al, 2007), H-gal-GP (Cachat et al, 2010;Smith et al, 2003) and Thiol separose binding proteins (TSBP) (Redmond and Knox, 2004) failed to induce a satisfactory immune response against H. contortus. This emphasizes the need to work for a more potential vaccine target against H. contortus.…”
Section: Introductionmentioning
confidence: 99%